Projects in dispute: contradictory public policies in the scope of Professional Education in Brazil (Research, Society and Development, 2019)
This article aims to make a brief historical rescue of some public policies of professional education in Brazil, revealing their contradictions. It starts from the educational policies of the 1990s that established the mandatory separation between high school and vocational education, intensifying the instrumental character in the field of professional education. In this educational perspective, we can see a process of exclusionary inclusion, since its disqualification, which includes in the labor market but excludes the possibilities that the subject has to acquire an onilateral and polytechnic education. In the accomplishment of this research, the bibliographical research was used, gathering, analyzing in an exploratory perspective, seeking to gather information about the themes of the projects that appeared in the history of Brazil about the Professional Education. In this way, a precarization of the work is legitimized from this continuity of precarious proposals of Professional Education. This precariousness that plagues this modality, provides a fragmentary, simplistic and technicist formation, providing a unilateral education to the detriment of onilateral formation. While omnilateral formation enables a formation that encompasses all dimensions of the individual broadly, in all his physical and intellectual capacities, unilateral formation fragments the individual so that he is only a subject specialized in manual work and favor the profit destined to the capitalist mode of production.